End-of-life Decisions In Malaysia: Adequacies Of Ethical Codes And Developing Legal Standards - Puteri Nemie Jahn Kassim; Fadhlina Alias (Thomson Reuters, 2024)
End-of-life decision-making is an area of medical practice in which ethical dilemmas and legal interventions have become increasingly prevalent. Decisions are no longer confined to clinical assessments; rather, they involve wider considerations such as a patient's religious and cultural beliefs, financial constraints, and the wishes and needs of family members. These decisions affect everyone concerned, including members of the community as a whole. Therefore it is imperative that clear ethical codes and legal standards are developed to help guide the medical profession on the best possible course of action for patients. This article considers the relevant ethical, codes and legal provisions in Malaysia governing certain aspects of end-of-life decision-making. It highlights the lack of judicial decisions in this area as well as the limitations with the Malaysian regulatory system. The article recommends the development of comprehensive ethical codes and legal standards to guide end-of-life decision-making in Malaysia.